Effect of Service Quality Dimensions on Students’ Satisfaction in Selected Chartered Universities in Kenya: A Multinomial Regression Application - Kimaita, Jane Naitore; Kabue, Hellen; Ochola, Phares; Kiriinya, Stephen Ntuara (Innovare Journal of Education, 2023)
The study sought to establish the effects of service quality dimensions on student satisfaction in selected chartered universities in Kenya. Service quality was measured under four dimensions: service tangibility, responsiveness, reliability, and accessibility on student satisfaction. A cross-sectional descriptive research design was employed Sampling was conducted in two stages: stage one was the sampling of the universities which were units of analysis, while stage two was sampling students from the sampled universities. Primary data was collected from 400 respondents. Descriptive statistics, namely; cross-tabulations and frequency distributions, were used to summarize the data, whereas inferential statistics were used to determine the relationship’s magnitude and direction. Statistical Package for Social Sciences (SPSS) was used for data analysis. The study used the Multinomial Logistic Regression (MLR) Model. The results revealed that service tangibility and responsiveness were statistically significant among the four hypotheses tested on the main effect MLR model.